Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/jcm9010162
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypoxemia Impacts Right Ventricle Diastolic Function in Obstructive Sleep Apnea: A Retrospective Observational Study

Abstract: Obstructive sleep apnea (OSA), although a growing healthcare problem and documented risk factor for cardiovascular diseases, is still under-diagnosed in cardiac patients. To investigate the correlation between OSA and echocardiographic parameters of right ventricle diastolic (RVD) dysfunction, in particular trans-tricuspid E-wave deceleration time (EDT), we retrospectively analyzed data of 103 pure (comorbidity-free) OSA patients with comprehensive echocardiographic examination (ETT). Apnea/hypopnea index (AHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…Another study published recently also showed that nocturnal hypoxemia is associated with right ventricle diastolic function in OSA 19 . Furthermore, OSA is also an independent risk factor for subclinical right ventricular dysfunction in children 19 . In our study, we found that the diameter of the pulmonary artery and right ventricle significantly increased with the severity of OSA, which might underly the right ventricular dysfunction.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Another study published recently also showed that nocturnal hypoxemia is associated with right ventricle diastolic function in OSA 19 . Furthermore, OSA is also an independent risk factor for subclinical right ventricular dysfunction in children 19 . In our study, we found that the diameter of the pulmonary artery and right ventricle significantly increased with the severity of OSA, which might underly the right ventricular dysfunction.…”
Section: Discussionsupporting
confidence: 77%
“…A previous study showed that right ventricular dysfunction reflected by RVEF is common in OSA, and it is reversible with the treatment of OSA 8 . Another study published recently also showed that nocturnal hypoxemia is associated with right ventricle diastolic function in OSA 19 . Furthermore, OSA is also an independent risk factor for subclinical right ventricular dysfunction in children 19 .…”
Section: Discussionmentioning
confidence: 97%
“… 14 Studies targeting RV function in the OSA setting based on conventional echocardiographic parameters reported mixed results. Some authors pointed out that patients with OSA frequently present RV structural and functional alterations, 15 , 16 others, on the contrary, failed to reveal significant morpho‐functional alterations of this cardiac chamber. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…14 Studies targeting RV function in the OSA setting based on conventional echocardiographic parameters reported mixed results. Some authors pointed out that patients with OSA frequently present RV structural and functional alterations, 15,16 others, on the contrary, failed to reveal significant morpho-functional alterations of this cardiac chamber. 17,18 In the last decade, RV strain, a parameter measuring myocardial deformation, has been recognized to provide a better evaluation of RV dysfunction than conventional echocardiographic parameters and, for this reason, it has been incorporated into contemporary echocardiographic guidelines for the assessment of RV performance.…”
Section: Introductionmentioning
confidence: 99%